2008
DOI: 10.1055/s-2007-965113
|View full text |Cite
|
Sign up to set email alerts
|

Time Limit at V·O2max Velocity in Elite Crawl Swimmers

Abstract: The purpose of this study is to assess, with elite crawl swimmers, the time limit at the minimum velocity corresponding to maximal oxygen consumption (TLim-vVO2max), and to characterize its main determinants. Eight subjects performed an incremental test for vVO2max assessment and, forty-eight hours later, an all-out swim at vVO2max until exhaustion. VO2 was directly measured using a telemetric portable gas analyzer and a visual pacer was used to help the swimmers keeping the predetermined velocities. Blood lac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
79
5
2

Year Published

2008
2008
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(99 citation statements)
references
References 19 publications
13
79
5
2
Order By: Relevance
“…Although its study only started in the last decade, investigations already were made on elite swimmers analyzing differences ; in both genders (Fernandes et al, 2005); in two performance levels ; with biomechanical factors in the front crawl technique (Fernandes et al, 2006b); in all four competitive strokes (Fernandes et al, 2006a); with biomechanical factors in breaststroke and butterfly techniques (Ramos et al, 2006); regarding intra cycle variation of velocity in all competitive strokes (Balonas et al, 2006) and regarding ventilatory threshold (Morais et al, 2006). The primary outcomes showed an inverse relationship between: Tlim-100%VO 2max and vVO 2max Fernandes et al, 2006a;Fernandes et al, 2008;Libicz et al, 2005); Tlim-100%VO 2max and energy expenditure for the entire group and for each gender (Fernandes et al, 2005); Tlim-100%VO 2max and SR in front crawl, butterfly and breaststroke techniques (Fernandes et al, 2006b;Ramos et al, 2006); Tlim-100%VO 2max and the velocity of anaerobic threshold (Fernandes et al, 2006a;Fernandes et al, 2008); Tlim-100%VO 2max and intra cycle variation of velocity in the front crawl and backstroke techniques (Balonas et al, 2006) and Tlim-100%VO 2max and body surface area and lactate production . Also the results of the studies reported direct relationships between: Tlim-100%VO 2max and the VO 2 slow component Fernandes et al, 2008); vVO 2max and C Libicz et al, 2005); Tlim-100%VO 2max and SL and SI in front crawl, butterfly and breaststroke techniques (Fernandes et al, 2006b;Ramos et al, 2006) and Tlim-100%VO 2max and intra cycle variation of velocity in the butterfly and breaststroke techniques (Balonas et al, 2006).…”
Section: Time Limitmentioning
confidence: 95%
See 1 more Smart Citation
“…Although its study only started in the last decade, investigations already were made on elite swimmers analyzing differences ; in both genders (Fernandes et al, 2005); in two performance levels ; with biomechanical factors in the front crawl technique (Fernandes et al, 2006b); in all four competitive strokes (Fernandes et al, 2006a); with biomechanical factors in breaststroke and butterfly techniques (Ramos et al, 2006); regarding intra cycle variation of velocity in all competitive strokes (Balonas et al, 2006) and regarding ventilatory threshold (Morais et al, 2006). The primary outcomes showed an inverse relationship between: Tlim-100%VO 2max and vVO 2max Fernandes et al, 2006a;Fernandes et al, 2008;Libicz et al, 2005); Tlim-100%VO 2max and energy expenditure for the entire group and for each gender (Fernandes et al, 2005); Tlim-100%VO 2max and SR in front crawl, butterfly and breaststroke techniques (Fernandes et al, 2006b;Ramos et al, 2006); Tlim-100%VO 2max and the velocity of anaerobic threshold (Fernandes et al, 2006a;Fernandes et al, 2008); Tlim-100%VO 2max and intra cycle variation of velocity in the front crawl and backstroke techniques (Balonas et al, 2006) and Tlim-100%VO 2max and body surface area and lactate production . Also the results of the studies reported direct relationships between: Tlim-100%VO 2max and the VO 2 slow component Fernandes et al, 2008); vVO 2max and C Libicz et al, 2005); Tlim-100%VO 2max and SL and SI in front crawl, butterfly and breaststroke techniques (Fernandes et al, 2006b;Ramos et al, 2006) and Tlim-100%VO 2max and intra cycle variation of velocity in the butterfly and breaststroke techniques (Balonas et al, 2006).…”
Section: Time Limitmentioning
confidence: 95%
“…The primary outcomes showed an inverse relationship between: Tlim-100%VO 2max and vVO 2max Fernandes et al, 2006a;Fernandes et al, 2008;Libicz et al, 2005); Tlim-100%VO 2max and energy expenditure for the entire group and for each gender (Fernandes et al, 2005); Tlim-100%VO 2max and SR in front crawl, butterfly and breaststroke techniques (Fernandes et al, 2006b;Ramos et al, 2006); Tlim-100%VO 2max and the velocity of anaerobic threshold (Fernandes et al, 2006a;Fernandes et al, 2008); Tlim-100%VO 2max and intra cycle variation of velocity in the front crawl and backstroke techniques (Balonas et al, 2006) and Tlim-100%VO 2max and body surface area and lactate production . Also the results of the studies reported direct relationships between: Tlim-100%VO 2max and the VO 2 slow component Fernandes et al, 2008); vVO 2max and C Libicz et al, 2005); Tlim-100%VO 2max and SL and SI in front crawl, butterfly and breaststroke techniques (Fernandes et al, 2006b;Ramos et al, 2006) and Tlim-100%VO 2max and intra cycle variation of velocity in the butterfly and breaststroke techniques (Balonas et al, 2006). Despite the previously described results, this thematic is still scarcely studied, and as a takehome message, it has not yet been related with the intra-cyclic variation of the horizontal velocity of the centre of mass and with the distribution of the percentage of energy contribution from each energy system.…”
Section: Time Limitmentioning
confidence: 95%
“…Each subject performed two distinct protocols in the crawl style, and an interval of 24 hours between them was respected. A progressive and interval protocol of 7 x 200 m, with 30 seconds of interval with increments of 0.05m.s-1 between each step 5,6 . The velocity of the last step was determined according to the performance hypothetically reached at that time at 400 m crawl, subtracting later to six intensity thresholds; swimming velocity was controlled with a light pacer (TAR 1.1, GBK -electronics, Aveiro, Portugal), placed in the bottom of the pool.…”
Section: Instruments and Proceduresmentioning
confidence: 99%
“…After determining the vVO 2max of each swimmer, followed by an adequate recovery period, applies the test of tlim-vVO 2max w h e n e a c h s w i m m e r t r y i n g t o s t a y i n y o u r s w i m m i n g v V O 2max (speed control) to exhaustion. The main studies in swimming suggest that tlim-vVO 2max : a. Correlates inversely with the energy cost, ie, it has a direct relationship with swimming economy (Fernandes et al 2005); b. Correlates inversely with the speed of the individual anaerobic threshold (Fernandes et al 2006a (Fernandes et al 2008); e. Shows no significant correlation with VO 2max (Fernandes et al 2003a;2003b;2005;2006a;2006b;2006c); f. Depends on the biomechanical parameters, correlating inversely with the strokes frequency and directly with the distance traveled per stroke cycle and the swimming index (product of the average SS and average distance traveled per stroke cycle) (Fernandes et al 2006b); g. During the protocol to obtaining tlim-vVO 2max there is a significant increase in stroke frequency and a great decline in the distance per stroke cycle (Marinho et al 2004(Marinho et al , 2006. Studies in runners and cyclists (Billat & Koralsztein 1996) found that the tlim-vVO 2max is less than 12 minutes, and the average is about 6 minutes.…”
Section: Tlim That Swimmers Are Able To Keep At Vvo 2max (Tlim-vvo 2mmentioning
confidence: 99%
“…Higher SS imply higher energy cost (Fernandes et al 2008); b. Higher vVO 2max in best swimmers require more strenuous levels of exercise, more anaerobic system request (Fernandes et al 2008). …”
Section: Tlim That Swimmers Are Able To Keep At Vvo 2max (Tlim-vvo 2mmentioning
confidence: 99%